Comparison of knowledge and perception about adverse drug reaction reporting and pharmacovigilance between pharmacy and medical students - B. T., Jeevan Gowda; B. T., Kruthika; M. G., Sneha; M., Kumaraswamy; B., Chandana (International Journal of Research in Medical Sciences, 2024)
Background: Adverse drug responses are serious public health issues worldwide. Pharmacovigilance (PV) is an important part of the healthcare system since it assesses, monitors, and discovers medication interactions and their consequences in humans. Objective were to assess knowledge and perception about adverse drug reactions (ADR) and PV among pharmacy and medical students. Methods: A cross-sectional study was conducted for pre-final year and final-year of pharmacy and medical students. Study conducted through semi structured questionnaires and a total 607 participants were recruited in this study. Results: A total 607 participants of pharmacy (52.5%) and medical (47.4%) from pre final (50.2%), final year (49.9%) students participated in this study. Pharmacy students had a significantly better overall knowledge of ADRs than medical students (p<0.05). The perception of pharmacy students regarding ADRs reporting and PV were significantly more than those medical student’s (p<0.05). In comparison to pharmacy students, a lack of knowledge of where and how to report ADRs was the main barrier that medical students perceived to ADR reporting (0.02). Conclusions: This study shows that compared to medical students, pharmacy students had better awareness of ADR reporting and shown good perceptions of PV. To enhance the knowledge of PV among healthcare students, an instructional intervention ought to be implemented.